NATIONAL MENTALITY AND CULTURAL ELEMENTS IN OFFICIAL DOCUMENT MANAGEMENT - Abduvaitov Eldorbek Farhod ogli (Modern American Journals, 2026)
This study examines the reflection of national mentality and cultural elements in the language of official documents. Although official documents are based on principles of neutrality, normativity, and legal precision, they are formed within a specific national cultural environment and therefore implicitly reflect social values, traditions of formal interaction, and norms of speech etiquette. The research demonstrates that national mentality is manifested in official discourse not through explicit emotional expression, but through institutionalized, standardized, and culturally balanced linguistic means. Particular attention is paid to forms of formal address, the expression of orders and requirements, the avoidance of personal subjectivity, and the maintenance of communicative distance. The study emphasizes the necessity of analyzing official documents from a linguocultural perspective, as such an approach allows official discourse to be interpreted not only as a technical or legal tool, but also as a linguistic phenomenon closely connected with national thinking and cultural memory. The findings contribute to revealing the internal cultural mechanisms of official document language and provide a theoretical basis for further research in linguocultural studies and official discourse analysis.
Keywords: Official documents; national mentality; linguocultural approach; official discourse; speech etiquette; cultural neutrality; national culture